Nickel(II) Ion Adsorption onto Activated Carbon. Relationship between Physicochemical Properties and Adsorption Capacity - Paola Rodríguez-Estupiñán; Liliana Giraldo; Juan Carlos Moreno-Piraján (Adsorption Science & Technology)
The adsorption of nickel(II) ions from aqueous solution onto various forms of granular activated carbon, GAC, has been studied. Thus, GAC was heat-treated at 900 °C (GAC 900), oxidized with HNO 3 (GACox), and this material subsequently heat-treated in an inert atmosphere at 450 °C and 750 °C (GACox 450 and GACox 750), all with the objective of changing the total acidity of the samples and demonstrating its influence on the adsorption capacity. The solids were characterized by N 2 and CO 2 adsorption isotherms from which the micropore volumes and surface areas were calculated — the latter being between 816 and 935 m 2 /g. In addition, some chemical characteristics such as the pH of the point of zero charge, the total acidity and basicity were examined, while immersion calorimetric studies in water were undertaken. The experimental results showed that the quantity of nickel(II) ions adsorbed onto the various GAC samples followed the order: GACox < GAC < GACox 450 < GACox 750 > GAC 900, indicating that the adsorption capacity depended largely on the surface acidity of the solid samples.